(untitled) (International Journal of Scientific Trends, 2026)
The mismatch between school education and labor market demands is a persistent challenge across developing and transitional economies. This paper presents the design, rationale, and international evidence base for a Smart Education and Job Market System – an AI-driven platform that integrates psychometric career assessment, personalized learning roadmaps, real-time labor market analytics, gamification, and multi-role dashboards for school students in Uzbekistan. Drawing on international best practices from Finland, South Korea, Singapore, and leading EdTech initiatives, the study demonstrates how artificial intelligence, explainable machine learning, and behavioral engagement mechanisms can collectively address the structural gap between adolescent career awareness and workforce requirements. The proposed system is positioned as a scalable, multilingual, and offline-capable solution for Central Asian educational contexts.